Further validation of the Traumatic Grief Inventory-Self Report (TGI-SR): A measure of persistent complex bereavement disorder and prolonged grief disorder. Issue 6 (3rd July 2019) - Boelen, Paul A.; Djelantik, A. A. A. Manik J.; de Keijser, Jos; Lenferink, Lonneke I. M.; Smid, Geert E.
Abstract: The Traumatic Grief Inventory Self-Report version (TGI-SR) is an 18-item self-report measure. It was designed to assess symptoms of Persistent Complex Bereavement Disorder (PCBD) included in Diagnostic and Statistical Manual of Mental Disorders (DSM)-5 and Prolonged Grief Disorder (PGD) proposed by an international group of experts in grief. The research in this article used data from a bereaved patient sample and people who lost loved ones in the Ukrainian airplane crash in July 2014. Findings indicated that the TGI-SR is a reliable and valid tool to assess disturbed grief in research and to identify people needing a more comprehensive assessment of their grief in clinical settings.